From Perception to Effect of Oil Spillage Among Fishermen in the Niger Delta Region of Bayelsa State, Nigeria - Akafa, Tensaba Andes; Asare, Solomon Ossom; Dennis, Adobeni Emmanuel; Konka, Daniel; Ametsi, Smile Kobina; Tahidu, Issifu; Oladele, Gloria Omonefe (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2025)
Oil spillage continues to pose a significant environmental threat in Nigeria’s Niger Delta, leading to ecological degradation, disruption of livelihoods, and socio-political instability. This study investigates the perceptions and impacts of oil spillage among fishermen in the Biseni community of Bayelsa State. Utilizing a descriptive cross-sectional design, data were collected from 358 respondents selected through systematic random sampling. A semi-structured, interviewer-administered questionnaire was employed, and responses were analyzed using SPSS version 16. The results show that 94.4% of respondents identified pipeline corrosion from soil-related factors as a major cause of oil spillage. Other commonly perceived causes included sabotage by surveillance contractors (86.3%), pipeline vandalism (85.2%), and unemployment (84.1%). Water pollution was identified by 98.0% of respondents as the most severe environmental consequence, particularly affecting aquatic life. Health impacts were also substantial, with 96.9% reporting adverse effects, skin rashes being the most frequently cited (32.0%). Economically, 95.5% of respondents reported reduced income due to declining fish yields. Broader socio-economic impacts included perceived links to unemployment (91.9%), increased kidnapping (79.6%), lack of compensation (80.4%), displacement (35.8%), and the need to purchase drinking water (70.4%). The study concludes that repeated oil spillage and unregulated exploitation have caused significant environmental and socio-economic harm in the Biseni community. The lack of effective compensation mechanisms intensifies local grievances and underscores the urgent need for sustainable environmental governance and enhanced corporate accountability in oil-producing areas.